(untitled) (Acta Scientiarum. Language and Culture, 2012)
Critics have recently addressed the work of T. S. Eliot in an innovative way. Instead of resorting to the same old epithets, ‘royalist, classicist, Anglo-Catholic,’ Eliot has been described as a poet who constantly challenged the very tradition he wished to preserve, confusing the limits between high and low cultures in his poems. Still, when it comes to introducing his work to the reader, manuals of literature are frequently eager to preserve the traditional image that scholars of Eliot have fought to challenge. From the analysis of Madame Sosostris’ appearance in The Waste Land, this essay intends to show how this movement of resistance to different Eliot works. In a few words, not to lose control over the place Eliot occupies as a modern poet, some manuals impose interpretations that, at times, cannot grasp the complexity of his lines.